Prestopanje meja - Dragoš, Srečo (Socialno delo, 2022)
After 60 years of publication of the Socialno delo journal (dedicated to social work), we found ourselves in a very unfavorable social environment. When the state and its systems do their job poorly, the quality of life deteriorates for everyone, but first of all for the marginalized groups and strata, because they have the least power. The same applies to the science system, where marginalized professions and institutions are most affected. How to act in such cases in social work, including our journal? A false dilemma that imposes itself (especially) in tough social conditions is in relation to professional standards. Are professions - as special, specialized fields that are within the social division of work clearly distinguished from other activities - only responsible for their own field that is their jurisdiction? Or is it more true that tampering with other systems in the environment is also part of professional responsibility? The article states the reasons for the second option, namely, that crossing the borders, not closing inward, is correct. There are three types of arguments: normative, generic and systemic.
Keywords: ethics; etika; fascism; fašizem; functionalism; funkcionalizem; profesija; profession; sistem; social work; socialno delo; system